Construction and Validation of Questionnaires on Reflective Practice and Teacher Professional Development - Porras Flores, Héctor (2020)
Objective. To construct and validate questionnaires on reflective practice and practicing teacher professional development. Method. It was a psychometric study of content validity and reliability through the application of a pilot test. 20 expert judges participated in the first measure. Data were processed by Aiken's V coefficient, confirming values by dimensions. Results. For the professional development variable, the values were: pedagogical = 0.97, social personal = 0.96, and institutional = 0.98. For the reflective practice variable, the values were: reflection in practice = 0.98, reflection on practice = 0.97 and reflection for practice = 0.98. Similarly, for the pilot test, 18 subjects participated according to the profile required by the research, obtaining reliability results alfa = 0.901 on 30 items of the professional development construct, and alfa = 0.948 on 20 items of the reflective practice construct. It has allowed to structure items and articulate criteria and dimensions for each variable of the research. Conclusion. The measurement result of the questionnaires is reliable.